The journalistic professionalization in Ecuador: The experience on the streets or the knowledge of the classrooms? - Punin Larrea, M. (2017)
This article discusses the current state of journalism in Ecuador and the predominant academic trends within schools and faculties of Social Communication in the country, spaces in which consolidates a professional profile whose role has been questioned. Concludes with an analysis of the need for training, updating and professionalization of the Ecuadorian journalism, taking as reference a survey applied to personnel with directives and journalistic functions of 2,944 media of Ecuador, within a national research project called: Map of the communication of Ecuador , developed by the Technical University of Loja.